Radiology of Castleman disease: the pivotal role of imaging in diagnosis, staging, and response assessment of this rare entity. Issue 6 (June 2022) - Din, F.; Mellor, F.; Millard, T.; Pace, E.; Khan, N.; Attygalle, A.D.; Cunningham, D.; Zafar, S.; Sharma, B.
Abstract : Castleman Disease (CD) is a rare entity that typically presents as an enhancing nodal mass in the mediastinum or head and neck region on computed tomography (CT). It may manifest as unicentric or multicentric regions of lymph node enlargement. A key clinical issue in the context of CD is delayed diagnosis, which contributes adversely to patient outcome, given that accurate diagnosis facilitates earlier treatment of this curable disease. This article will address relevant imaging aspects, with reference to typical and atypical imaging features of CD, illustrated using examples from our specialist centre; the imaging journey for patients with CD; and will provide practical pointers to radiologists in differentiating CD from other benign and malignant causes of enhancing lymphadenopathy, including lymphoma and neoplastic adenopathy. We will also review current classification tools and staging challenges with reference to World Health Organization guidelines, International Working Group guidelines as well as the Lugano classification. Finally, we will discuss the potential role of additional imaging techniques in CD, highlighting novel imaging methods and expanded utilities from our specialist centre.